Exports, unemployment and the welfare state - Eckhard Janeba (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2007)
The paper analyzes the labor market effects of globalization when foreign market entry is costly and risky. With flexible labor markets, a fall in foreign market entry cost tends to generate more income inequality. By contrast, when workers cannot easily switch industries and wages are inflexible in the short run, globalization tends to increase unemployment. In this situation, government unemployment benefits reduce the wages that exporting firm's need to pay workers as risk compensation. Thus more firms within an industries and more industries become exporters. The above findings are consistent with popular views about the globalization effects in the U.S. and continental Europe. The results also suggest that the welfare state can simultaneously cause an increase in unemployment and exports.
Keywords: D4; F1; H2; 330; income inequality; unemployment; exporters; beachhead costs; globalization; Globalisierung; Beschäftigungseffekt; Einkommensverteilung; Arbeitslosigkeit; Außenhandelswirtschaft; Sozialstaat; Arbeitslosenversicherung; Theorie